2004
DOI: 10.1158/1078-0432.ccr-04-0337
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Methylation of DPYD Promoter, DPYD Expression, and Cellular Sensitivity to 5-Fluorouracil in Cancer Cells

Abstract: Purpose: Dihydropyrimidine dehydrogenase (DPD), the initial rate-limiting enzyme in the degradation of 5-fluorouracil (5-FU), is known to be a principal factor in clinical responses to the anticancer agent 5-FU, and various reports have clearly demonstrated that DPD activity is closely correlated to mRNA levels. However, the regulatory mechanisms of DPD gene (DPYD) expression remain unclear. In this study, the regulatory mechanisms have been intensively studied.Experimental Design and Results: A subcloned 3.0-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 15 publications
3
34
0
Order By: Relevance
“…Studies in cancer cell lines (oral epidermoid carcinoma line KB, colon adenocarcinoma COLO20, oral squamous cell carcinoma lines HSC3, HSC4, and Ca9-22 and hepatoma HepG2 cell lines) showed the absence of genetic alterations in DPYD promoter region with full activity (8). Our results show the absence of DNA sequence variants in the DPYD promoter region in all studied individuals.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Studies in cancer cell lines (oral epidermoid carcinoma line KB, colon adenocarcinoma COLO20, oral squamous cell carcinoma lines HSC3, HSC4, and Ca9-22 and hepatoma HepG2 cell lines) showed the absence of genetic alterations in DPYD promoter region with full activity (8). Our results show the absence of DNA sequence variants in the DPYD promoter region in all studied individuals.…”
Section: Discussionsupporting
confidence: 57%
“…Recent advances in our understanding of molecular mechanisms involved in the activation and degradation of 5-FU have led to an increased awareness of the potential importance of epigenetic factors in deciding the sensitivity of patients to anticancer drugs. We hypothesize that in the absence of inactivating mutations, methylation of CpG islands located in the 5V regulatory region of the DPYD gene promoter, may inhibit the binding of transcriptional factors or stabilize the chromatin structure, thereby directly inhibiting transcription (8).…”
mentioning
confidence: 99%
“…Despite its easiness, many contradictory results regarding the predictive power of expression analyses were obtained [38,39]. The influence of DPYD promoter methylation on DPYD gene expression was also considered, however contrary to initial reports latest studies demonstrated limited or no methylation of DPYD promoter in high-toxicity patients [27,[40][41][42]. The most common concept for prediction of serious toxicity in 5-FU-treated patients represents pharmacogenomic analyses.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a general consensus that there can be some discrepancies among mRNA, protein expressions and the enzyme activity, because there can be several regulatory mechanisms including posttranscriptional and posttranslational regulation in the expression of a gene and also there can be a conditional regulation concerning the enzyme activity. Regulatory mechanism of DPD activity may be associated with negative-feedback system, regulation by transcriptional factor of DPD gene, such as AP-1, 48 methylation of the promoter region 49 or unknown DPD inhibitor. Further investigation should be required for precise explication of regulatory mechanism of DPD activity.…”
Section: Discussionmentioning
confidence: 99%